Application of the Iqro' Method as a Basic Ability to Read the Qur'an at Sri Tengo Wittaya School - Sikumbang, Ibnu Khotim; Lubis, Jumaita Nopriani; Sormin, Darliana (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
The ability to read the Koran is an urgent matter for Muslims. The Koran is also the first holy book and guideline for Islamic law. Teaching children to read the Koran is not easy, because apart from requiring knowledge, an educator must also know the methods that can be used in the learning process. The iqro method has been known as an effective learning approach in helping students understand and read the Koran. This research aims to determine the application of the iqro method as a basic ability to read the Al-Quran at Sri Tengo Wittaya School. This research is in the form of qualitative research. Data collection tools include interview guides, observation and documentation to obtain data and analyze it. From the research results, there is an increase in the ability to read the Al-Qur'an using the Iqro method at Sri Tengo Wittaya School, this shows that the majority of students enjoy learning the Al-Quran using the Iqro method so that they are able to read the Al-Qur'an fluently and reciting tajwid the good one.